Changes in Acidity, TSS, and Sugar Content at Different Storage Periods of the Postharvest Mango (Mangifera indica L.) Influenced by Bavistin DF - Md. Khairul Islam; M. Z. H. Khan; M. A. R. Sarkar; Nurul Absar; S. K. Sarkar (International Journal of Food Science)
A detailed study was carried out with the postharvest mangoes (namely, the Langra and the Khirshapat) treated with different levels of Bavistin DF (BDF) solution (namely, 250, 500, and 750 ppm) for obtaining results on biochemical changes as well as storability of postharvest mango. The experiment was laid out in randomized complete block design with three replicates. The results of the experiments exhibited that only the single effect of varieties was found to be significant in most of the parameters studied. The Langra enriched a greater quantity of titratable acidity and total soluble solid (TSS) at 3rd day, over the Khirshapat. On the other hand, Khirshapat showed increased pulp pH and TSS at all the storage duration. The results explored that some physicochemical properties, namely, pulp pH, TSS, sugar (total, reducing, and nonreducing), and titratable acidity along with shelf life drastically decreased from untreated mangoes. Bavistin DF with the doses of 750 ppm showed better results in delaying the changes in physicochemical properties and extended shelf life.